EXPERT SYSTEM DIAGNOSING STROKE TRANSIENT ISCHEMIC ATTACK (TIA) USING THE WEB-BASED DEMPSTER SHAFER METHOD - Aminun Aminun; Akmal Nasution; Bachtiar Efendi (Jurnal Teknik Informatika (Jutif), 2022)
The neurologist at RSUD Dr. Tengku Mansyur Tanjungbalai City has changed working hours during the Covid 19 pandemic, making people who want to seek treatment and consult to overcome complaints of Stroke Transient Ischemic Attack (TIA) into confusion and RSUD Dr. Tengku Mansyur Tanjungbalai City limits the number of patients in consulting for Stroke Transient Ischemic Attack (TIA) to avoid crowds. To overcome these problems, an expert system was created using the Dempster Shafer method. The purpose of this study is to create an expert system that makes it easier to diagnose Stroke Transient Ischemic Attack (TIA) disease. The research method used in this study is quantitative, namely research that uses data in the form of numbers that are processed using a formula so as to obtain results based on calculations with that formula. The purpose of this research method is to describe the object under study, namely data on Stroke Transient Ischemic Attack (TIA), based on the results of the calculation of the Dempster Shafer method. An expert system that can be accessed online by patients with Stroke Transient Ischemic Attack (TIA) because it is designed using the PHP programming language and MySQL database. As a result an expert system using the Dempster Shafer method which provides a consultation feature for patients with Stroke Transient Ischemic Attack (TIA) making it easier for patients to find solutions to the symptoms they are experiencing.. The more often patients do consultations, which will increase public awareness about the disease.